IMPLEMENTASI MODEL LRD (LISTEN-READ-DISCUSS) UNTUK MENINGKATKAN MAHARAH QIRA’AH MAHASISWA PPBA FAKULTAS HUDAYA UNIVERSITAS ISLAM NEGERI MAULANA MALIK IBRAHIM MALANG - Anita Andriya Ningsih (El-QUDWAH, 2014)
Oleh: Anita Andriya Ningsih, Pusat Pengembangan Bahasa Arab Universitas Islam Negeri Maulana Malik Ibrahim Malang email: banoriss@yahoo.co.id   ABSTRACT Generally,  this  research  is  aimed  at  improving  students’ reading comprehension by implementing the LRD (Listen-Read-Discuss) teaching method. Subjects of the research are the students of  2013/2014 academic year taking reading II subject. The research uses classroom action research method. The data are collected by reading comprehension test for measuring the students’s reading comprehension and questionarrie with Liket scale for collecting the students’ perceptions toward LRD  (Listen-Read-Discuss) teaching method. The data are analyzed by descriptive technique. The results of research show that 1) the preliminary comprehension of the students’ reading comprehension is relative poor and very poor in which the  distribution of comprehension is not proportional, 2) After first cycle, the students’ reading comprehension improve relativel significantly, 3) Then, after the end of the research, the students’ reading comprehensions improve significantly which most of them (52,8) obtains grade B or  it is categorized good and (8,3%) reaches grade A. Only about (33,33%) and (2,8%) of them still have grade C and D. However, nobody gets failed.  In term of perception, generally the students have positive and good responds and perception toward the LRD  (Listen-Read-Discuss) teaching method for teaching and learning reading comprehension subject.   Keywords: LRD  (Listen-Read-Discuss), Reading II